O Uso das TICs e da Pesquisa como Recursos Pedagógicos no Ensino de Bioquímica para o Curso de Licenciatura em Química - Lima, Emmanuela Ferreira de (Revista de Graduação USP, 2017)
With the advent of the technology, the use of notebooks, tablets and smartphones has increased every day and the society has been adapting itself to these changes in all areas of knowledge and it could not be different in teaching. The Information and Communication Technologies (ICTs) have become an important tool of aid in the learning, being able to give dynamism to the classes and to arouse the interest of the students also in higher education as well. Associated to ICTs, this research provides an active participation of the students in the search for knowledge, helping in their intellectual and personal growth, giving more autonomy and confidence in the approach of certain contents. The objective of this work is to report the experience in the discipline of Biochemistry that belongs to the seventh period of the Chemistry degree of the Instituto Federal Goiano, campus Morrinhos, Goiás, regarding the use of computer programs and research as tools in the study of the proteins. The results obtained were very positive, showing that ICT, associated with research in higher Chemistry and Biochemistry education can be used as an alternative to improve teaching methodologies and student learning.